Islamic Educational Values in the Yasin Recitation Tradition - Anggriya Utami; Kasimaldi; Linda Suanti; Budi Santoso (Al-Kahfi: Jurnal Pendidikan Agama Islam, 2026)
This research is motivated by the routine of Wirid Yasinan Jorong Padang Tujuh West Pasaman held every Saturday, different from the Yasinan tradition carried out by the community in general. Saturday was chosen because on that day some people do not work and do not have much activity. In the routine of Wirid Yasinan Jorong Padang Tujuh West Pasaman, a question and answer session was held regarding daily religious problems experienced by the community. Wirid Yasin was first formed in West Pasaman in 2000 and was hiatus for several years, then reactivated in 2019. Based on the results of the research conducted, the researcher concluded that 1) the value of Islamic Education in the Wirid Tradition in Jorong Padang Tujuh West Pasaman. The Islamic educational values ​​contained in the wirid tradition in Jorong Padang Tujuh, West Pasaman are as follows: a) Studying matters of worship, b) The value of practicing faith, c) The value of moral education, 2) Inhibiting factors encountered in the implementation of the Yasin recitation in Jorong Padang Tujuh, West Pasaman: a) Lack of infrastructure, and b) Community activities. 3) Community understanding. It can be seen that the implementation of the Yasin recitation tradition can realize spiritual awareness, such as increased faith, the acquisition of knowledge, blessings, and brotherhood.